1992
DOI: 10.1016/0378-1097(92)90634-z
|View full text |Cite
|
Sign up to set email alerts
|

Acid phosphatase activity of promastigotes of Leishmania donovani: a marker of virulence

Abstract: Seven cloned lines of promastigotes of Leishmania donovani (UR 6) were isolated by limiting dilution. One clone, UR6-C25, failed to multiply inside the macrophages of line J774G8 and thus was labelled as avirulent. Another, UR6-C24, multiplied inside macrophages, had a virulence index as high as 93 +/- 9.8 and was thus labelled as highly virulent. The other five clones had variable degree of virulence indices ranging from 46.4 +/- 5.8 to 67.6 +/- 3.5. No significant difference in the degrees of attachment of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0
2

Year Published

1994
1994
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 26 publications
4
23
0
2
Order By: Relevance
“…In other parasites, acid phosphatase has been proposed as a virulence factor [59], [60], [61], [62]. However, the AcPh from Giardia does not seem to be secreted, even in contact with intestinal cells [63].…”
Section: Discussionmentioning
confidence: 99%
“…In other parasites, acid phosphatase has been proposed as a virulence factor [59], [60], [61], [62]. However, the AcPh from Giardia does not seem to be secreted, even in contact with intestinal cells [63].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Coxiella burnetti and Entamoeba histolytica secrete molecules with AcP activity and this activity possesses PTPase activity (Baca et al 1993;AnayaRuiz et al 2003). In L. donovani, it has been shown that an acid phosphatase cloned from promastigotes correlated with the degree of virulence (Singla et al 1992). …”
Section: Discussionmentioning
confidence: 99%
“…Proteases, acid phosphatases, superoxide dismutases, heat-shock proteins and other 'stress' proteins are often important virulence factors in parasitic protozoa of vertebrates and invertebrates (Katakura 1986, Katakura & Kobayashi 1988, Hervio et al 1991, Singala et al 1992, Vannier-Santos et al 1995, Wiese 1998, Volety & Chu 1997. Many of these proteins have been used to characterize virulence in relation to disease.…”
Section: Biochemistry Of Infectionmentioning
confidence: 99%